Fuzzy Ontology-based Semantic Integration of Heterogeneous Data Sources in the Domain of Watershed Analysis - Ferraz, Vinícius R. T.; Afonso, Gustavo F.; Yaguinuma, Cristiane; Borges, Sérgio; Santos, Marilde T. P. (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2010: Anais do II Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais, 2010)
In environmental research, data integration plays an important role given the increasing availability of heterogeneous data sources for specific features, such as soil type, climate, geographic location and so on. However, some of those features have inherently imprecise relationships and the lack of a suitable semantic model can be a major obstacle to its effective integration. In this context, this paper presents a semantic data integration system based on a fuzzy ontology, capable of perform query expansions based on imprecise aspects of real phenomena. We executed a real experience in the domain of watershed analysis. Consequently, watershed researchers obtained an homogeneous view of the data sources and more effective responses to their queries.